Gender-related differences on outcome following transcatheter mitral valve repair (TMVR): a systematic review and meta-analysis - Kang Yi; Jie Gao; Wen-Xin Wang; Yu-Hu Ma; Wei Wang; Shao E. He; Xiao-Min Xu; Peng-Fei Li; Tao You (Journal of Cardiothoracic Surgery, 2023)
Abstract Background The effect of gender on patients with mitral valve regurgitation (MR) undergoing transcatheter mitral valve repair (TMVR) remains to be defined. The aim of the present study is a comprehensive meta-analysis of studies that investigate differences between men and women after TMVR. Methods A systematic literature search was carried out on eight databases to collect all relevant studies on gender-related outcomes of TMVR before March 1, 2021. The main outcomes of interest were mortality, cardiac function, MR class and other complications. Results A total of eight literatures were included, all of which were retrospective observational studies. Compared to women patients, men had lower postoperative New York Heart Association (NYHA) class (OR = 1.53, 95%CI [1.23, 1.91], P = 0.0001) and higher incidence of postoperative acute kidney injury (AKI) (OR = 1.25, 95%CI [1.16, 1.34], P < 0.05). There were no significant difference on mortality in 30 days (OR = 0.95, 95%CI [0.81, 1.11], P = 0.53) and in 2 years (OR = 0.99, 95%CI [0.75, 1.30], P = 0.93), mitral valve regurgitation (MR) class (OR = 1.30, 95%CI [0.97, 1.75], P = 0.08) and incidence of myocardial infarction (MI) (OR = 0.88, 95%CI [0.65, 1.18], P = 0.38), stroke (OR = 0.80, 95%CI [0.63, 1.02], P = 0.08) and bleeding in hospital (OR = 0.84, 95%CI [0.59, 1.19], P = 0.32). Conclusions Our meta-analysis demonstrates that men undergoing TMVR have worse preoperative diseases (diabetes mellitus, coronary artery disease, renal failure and myocardial infarction) while they have superior postoperative NYHA class at one-year. There are no significantly difference in other indexes between men and women.